1970
DOI: 10.1042/cs0390549
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Fibrinolytic Enzyme System in Renal Disease

Abstract: 1. Levels of serum inhibitor of plasminogen activation, anti-plasmin and plasminogen activator were measured in normal subjects and patients with active glomerulonephritis and chronic renal failure.2. Patients with active glomerulonephritis all had grossly elevated levels of serum inhibitor of plasminogen activation and significant elevation of anti-plasmin. The majority of activator levels lay at the lower end of the normal range.3. Patients with chronic renal failure had significantly elevated levels of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
(25 reference statements)
2
1
0
Order By: Relevance
“…This result was in agreement with several studies conducted among hypertensive patients [8] [11] [12]. Also this finding is contrary to the findings reported by other workers [13] [14]. Although Sechi et al did not observe differences in fibrinogen between hypertensive patients and normotensive controls, their study demonstrated a strong and independent association between fibrinogen and the presence and severity of hypertension related damage in different target organs [15].…”
Section: Discussionsupporting
confidence: 86%
“…This result was in agreement with several studies conducted among hypertensive patients [8] [11] [12]. Also this finding is contrary to the findings reported by other workers [13] [14]. Although Sechi et al did not observe differences in fibrinogen between hypertensive patients and normotensive controls, their study demonstrated a strong and independent association between fibrinogen and the presence and severity of hypertension related damage in different target organs [15].…”
Section: Discussionsupporting
confidence: 86%
“…Of interest is the increased activity of urokinase inhibitor, demonstrated in seven of the eight patients. A similar abnormality has previously been reported in the serum of individuals with various renal disorders (Bennett and Ogston, 1970) and it is possible that the development of this inhibitor is related to the deposition of fibrin within the glomerular capillaries.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is evident from table I that a trend in mean values of each parameter was similar in the hypertensive and normotensive patients with renal disease. Rastogi, 1970;Bennett and Ogston, 1970), but their relationship to the development of hypertension was not considered in these studies. The relationship of changes in the fibrinolytic enzyme system to the development of hypertension is not clear.…”
Section: Discussionmentioning
confidence: 99%